Lipid Peroxidation - Catala, Angel (IntechOpen, 2012)
The purpose of this book is to concentrate on recent developments on lipid peroxidation. The articles collected in this book are contributions by invited researchers with a long-standing experience in different research areas. We hope that the material presented here is understandable to a broad audience, not only scientists but also people with general background in many different biological sciences. This volume offers you up-to-date, expert reviews of the fast-moving field of Lipid Peroxidation. The book is divided in four mayor sections: 1-Lipid peroxidation: chemical mechanisms, antioxidants, biological implications; 2-Evaluation of lipid peroxidation processes; 3-Lipid peroxidation in vegetables, oils, plants and meats and 4-Lipid peroxidation in health and disease.